STUDENTS’ THINKING PROCESSES IN SOLVING OPEN-ENDED PROBLEMS USING ONLINE LEARNING TAKING INTO ACCOUNT THE MATHEMATICAL ABILITY - Tigas Laila Nurpratiwi; Rini Setianingsih (Pi: Mathematics Education Journal, 2021)
It is important for a student to be able to solve problems. This study aims to describe students’ thinking processes in solving open-ended problems with online learning reviewed from mathematical abilities. This research is descriptive in nature with a qualitative approach. The subjects of this research consist of three 8th grade students, while the research instruments that were used consist of a mathematical ability test, an open-ended problem test and interview guideline. The results of the study reveal that student with high mathematical abilities meets all indicators of thinking processes, while student with average mathematical ability at the step of understanding the problem, did not carry out of making arguments, at the step of devising a plan he did not carry out the considering thinking process, as well as did not give an argument at the step of looking back. Almost the same as these results, student with low mathematical ability did not carry out the thinking process of remembering and the process of considering, while at the step of looking back, he did not carry out the process of considering and making an argument. Based on these results, it can be concluded that mathematical ability affects a student’s thinking process.